Pengaruh Likuiditas dan Variabel Eksternal Terhadap Non Performing Financing Pada Bank Syariah - Pradana, Mochammad Nugraha Reza (STIE PGRI Dewantara Jombang, 2018)
Increasing the value of Non Performing Financing (NPF) Sharia Commercial Banks will pose a threat to the Islamic Financial Industry in Indonesia. Whereas the Sharia Commercial Bank as an illustration of the Indonesian Sharia Financial Industry must continue to compete with Conventional Banks that were previously present in Indonesia. The increase in NPF must be suppressed by the Management of Islamic Commercial Banks in Indonesia so as not to keep moving up so that it sinks the Indonesian Islamic Financial Industry. There are several influences such as Bank Liquidity and External Variables which are thought to influence NPF Sharia Commercial Banks in Indonesia. The purpose of this study is to determine how the effect of liquidity is proxied by Financing to Deposit Ratio (FDR), Financing to Asset Ratio (FAR), and Reserve Requirement (RR) and also the influence of external variables such as inflation and exchange rates on NPF. To solve this problem, multiple linear regression analysis techniques are used. This research was conducted at Sharia Commercial Banks in Indonesia registered in 2012-2015. Based on the results of the analysis, it is known that FDR and FAR have a positive effect on NPF while RR, Inflation, and Exchange Rate have no effect on NPF Sharia Commercial Banks in Indonesia.